Mauritius : Report on Observance of Standards and Codes-Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2008)
This report on the observance of Standards and Codes-Data Module provides an assessment of Mauritius's macroeconomic statistics against the Special Data Dissemination Standard complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework July 2003. The assessment reveals that the quality of the macroeconomic statistics in Mauritius has improved significantly since the previous assessment conducted in 2001. Quarterly national accounts were successfully put in place. Work is well advanced to implement the new international methodology for government finance statistics.